2016
DOI: 10.1111/cpr.12271
|View full text |Cite
|
Sign up to set email alerts
|

Primordial germ cell–like cells derived from canine adipose mesenchymal stem cells

Abstract: This study provides an efficient approach to study germ cell development using CAMSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…A previous study with human ovarian MSC also demonstrated the ability of those cells to differentiate into mesenchymal, ectodermal and endodermal lineages, concurring with our results describing the high differentiation potential of the cells from the ovary . Canine adipose‐derived stem cells have already been shown to differentiate into germ cells, so our next step was to verify if the cells derived in the present paper also possessed the capability to differentiate into putative germ cells by using the culture conditions for female germ cells derived from the ovary of neonatal mice . After 2 weeks in this media, the cells changed their morphology from fibroblast‐like to colonies of rounded cells that were positive for OCT4 and DDX4 by immunocytochemistry.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study with human ovarian MSC also demonstrated the ability of those cells to differentiate into mesenchymal, ectodermal and endodermal lineages, concurring with our results describing the high differentiation potential of the cells from the ovary . Canine adipose‐derived stem cells have already been shown to differentiate into germ cells, so our next step was to verify if the cells derived in the present paper also possessed the capability to differentiate into putative germ cells by using the culture conditions for female germ cells derived from the ovary of neonatal mice . After 2 weeks in this media, the cells changed their morphology from fibroblast‐like to colonies of rounded cells that were positive for OCT4 and DDX4 by immunocytochemistry.…”
Section: Discussionsupporting
confidence: 89%
“…The isolated cADMSCs are positive for CD73, CD105 (Fig. S2), CD44, CD90 and CD166, whereas negative for CD34 and CD45; these cells could also differentiate into adipocytes, osteoblasts and chondrocytes under induction conditions16.…”
Section: Methodsmentioning
confidence: 98%
“…However, a two‐step culture method using 25 ng/ml of BMP4 for 5 days followed by 1 μM of RA for 12 days induced DAZL and STRA8 expression in mice MSC (Afsartala et al., ). Canine adipose tissue (AT) MSC, treated for 7 days with 12.5 ng/ml of BMP4, increased expression of PGC markers PRDM1, PRDM14 and male GC markers DMRT1 and PLZF but showed no effect on VASA expression (Wei et al., ). Overall, these results suggest that BMP4 regulation of GC gene expression may vary, according to concentration and time in culture medium.…”
Section: Discussionmentioning
confidence: 99%